Associations between Sociodemographic and Behavioral Variables and Educational Practices on Mother-Child Dyads - Bolsoni-Silva, Alessandra Turini [UNESP] (2023)
The association between the sociodemographic variables of children with behavior problems and mothers with maternal depression is widely acknowledged in the literature. However, there is a lack of studies addressing the association of these variables with maternal parenting practices in typical samples, i.e., children without behavior problems and mothers without current depression indicators. The aim of this study was to identify associations between the sociodemographic variables of children and mothers with the mothers’ parenting practices and children’s behavioral indicators (resources and problems) in a sample of children without behavior problems and mothers without current depression indicators. This quantitative, cross-sectional, descriptive, and correlational study addressed 46 biological mothers (married or in a stable relationship) and their children. A sociodemographic questionnaire and validated instruments addressing child behavior, maternal mental health, and parenting practices were applied. Findings showed that the mothers did not present mental health problems (e.g., behavior problems or maternal depression), but a) they presented deficits of positive practices and an excess of negative practices, and the children displayed deficits in social skills and behavior problems; b) there was an association between positive practices and the children’s social skills and between negative practices and children’s behavior problems; c) the frequency of positive and negative practices was equivalent among boys and girls, and d) boys more frequently presented behavior problems while school-aged children more frequently presented social skills deficits. The results indicate that even non-clinical samples may present harmful parenting practices, excess negative practices, and deficits in positive practices. Hence, there is a need for timely interventions to prevent behavior problems among children and maternal depression aris-ing from conflicting interactions in the parenthood sphere.